PERSPEKTIF TENTANG MAKNA BAIK DAN BURUK - Hafid Rustiawan (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2019)
Good and bad are antonyms words, which are used to judge or measure a state or thing and human actions. Values ​​based on these measures are qualitative and global, so that they become areas of ethical study. Likewise in Islam these two terms become one of the central discussions in Islam, so that in the Koran many identical terms are often used, for example khoir and hasan, al-toyyib, while the bad terms use al-qubh and al-syar , al-sa and al-khobits, and among Muslim theologians, the terms good and bad are also one of the topics of his study, such as Mu'tazilah and Ash'ariah. The concepts of good and bad in Ash'ariah theology, and Mu'tazilah have similarities and differences. The similarity is that the two schools agree that what is said to be good is what gives rise to good in the world, and in the hereafter, while the difference is in terms of the source of goodness. The Ash'ariah School, argues that the source of goodness is revelation from God, because only God is the only one who knows the effect of goodness, whereas according to the Mu'tazilah, the source of goodness is not only revelation, but also reason, because reason is a human resource that very large which gives instructions. Thus, good and bad in Islamic theology are very clear, because they come from revelation, but reason also becomes one of the sources when it does not conflict with revelation.